LEADING PRINCIPLES IN THE POETRY OF UZBEK POETS IN NORTHERN AFGHANISTAN - Mirwais Turk (Innovate Conferences, 2025)
This article discusses the leading principles found in the poetry of Uzbek poets who lived and worked in northern Afghanistan and their reflection in fiction. The principles found in the poets' work are classified and compared with the poetry of Turkic peoples.
Keywords: literature, fiction, Turkic literature, poet, poetry, principle, guiding principle, classification, comparative analysis.